Pelatihan dan Pendampingan Usaha di Kelompok Pengolahan dan Pemasar Hasil Perikanan (POKLAHSAR) di Dusun Lokok Rangan, Kecamatan Kayangan, Kabupaten Lombok Utara - Sulaimiah Sulaimiah; Santi Nururly; Sulhaini Sulhaini; Djoko Suprayetno (Universitas Mataram, 2020)
North Lombok Regency is the most affected area due to the sequential earthquake that occurred in July 2018 on the island of Lombok. Therefore, the purpose of community service activities is to provide training and business assistance to communities that have an impact on earthquakes. The location is addressed to the Sedayu Putri Fisheries Processing and Marketers Group (POKLAHSAR) on Lokok Rangan Hamlet, Kayangan District, North Lombok Regency. The training provided on entrepreneurship and business management to produce a variety of food products from marine fish, such as shredded meat, fish bone crackers and fish bone sticks from the utilization of fish bone waste. Next to provided training on marketing and finance. The method used by lectures, consultation and assistance. Activities will be carried out from May 2019 to November 2019. The results of the activities of group members are able to produce shredded fish products, fish bone crackers and fish sticks. Expected result is the participants rose again to produce a variety of processed products from the sea acquired knowledge about the importance of packaging, used social media for broad marketing, and made financial report. Participants got back up from adversity and generated income to improve their welfare.